Colleges of Education Pre-Service Teachers’ Awareness, Readiness, and Accessibility Levels with Intelligent Tutoring Systems in North-Central, Nigeria - Hameed Olalekan Bolaji; Abdulahi Adedolapo Ahmed (Universal Education Jurnal Teaching and Learning, 2025)
Intelligent Tutoring Systems (ITS) are automated teaching tools that leverage artificial intelligence to interact with students directly and deliver customised learning experiences, substituting the instructional tasks typically handled by human educators. However, a gap exists in understanding the current state of ITS among pre-service teachers of Colleges of Education in Nigeria. This research sought to investigate the awareness, readiness and accessibility levels regarding ITS among pre-service teachers. Specifically, the study examined: (i) the awareness level of ITS among pre-service teachers; (ii) the readiness level of pre-service teachers towards ITS; and (iii) the accessibility level of pre-service teachers to use ITS. The research employed descriptive research of the cross-sectional survey design using a quantitative approach. The population consisted all pre-service teachers in all the Colleges of Education in North Central Nigeria. Multistage sampling techniques were used to select the representative samples of 656 pre-service teachers from the target population of 40,148 from 20 Colleges of Education across six states and the Federal Capital Territory. Data were collected using a researcher-designed questionnaire and were further analysed using descriptive and inferential statistics. The significance level was set at 0.05, and the instrument’s reliability and validity were ensured through expert reviews and pilot testing. The study revealed that: i. Pre-service teachers are moderately aware of Intelligent Tutoring Systems; ii. Pre-service teachers have a positive readiness towards the use of ITS; iii. The finding implies that college ownership and school of discipline, play a crucial role in influencing the effective adoption of ITS. This study recommends training programmes for pre-service teachers to enhance ITS awareness and readiness, improvement of technological infrastructure to increase accessibility and incorporation of collaborative tools to foster engagement among pre-service teachers.